Unnatural substrates reveal the importance of 8-oxoguanine for in vivo mismatch repair by MutY - Livingston, Alison L. (2007)
Escherchia coli MutY plays an important role in preventing mutations associated with the oxidative lesion 7,8-dihydro-8-oxo-2′-deoxyguanosine (OG) in DNA by excising adenines from OG:A mismatches as the first step of base excision repair. To determine the importance of specific steps in the base pair recognition and base removal process of MutY, we have evaluated the effects of modifications of the OG:A substrate on the kinetics of base removal, mismatch affinity and repair to G:C in an Escherchia coli-based assay. Surprisingly, adenine modification was tolerated in the cellular assay, while modification of OG results in minimal cellular repair. High affinity for the mismatch and efficient base removal require the presence of OG. Taken together, these results suggest that the presence of OG is a critical feature for MutY to locate OG:A mismatches and select the appropriate adenines for excision to initiate repair in vivo prior to replication.